Substance Use and Associated Experiences of Intimate Partner Violence Among MSM in Los Angeles, California - Miller, Amanda Pearl (Journal of interpersonal violence, 2024)
This study examined the prevalence and correlates of intimate partner violence (IPV) among a cohort of racial/ethnically diverse men who have sex with men (MSM) in Los Angeles. An ongoing longitudinal cohort study of MSM in Los Angeles, constructed by design so half of the participants use substances (SU) and half are persons living with HIV, provided data. Data collection occured between 2014 and 2020. At semiannual study visits, participants completed a computer-assisted self-interview which included questions on substance use (past 6 months) and experiences of IPV (past 12 months). The criterion variable was reported physical and sexual IPV. Multivariable models generalized estimating equations (GEE) estimated associations between reported SU and physical and sexual IPV, adjusting for repeated measurement and confounders. In total, 557 persons (2,962 visits) contributed to the analysis; the median baseline age was 30 years (interquartile range: 28.0–39.0). The prevalence of IPV in the past 12 months was 22.3%, with 18.3% reporting physical and 10.2% reporting sexual IPV across study visits. Stimulant use prevalence was higher among those who reported IPV compared to those who did not (68% vs. 42.1%; p < .001); cannabis use prevalence was lower among those reporting IPV (42.3% vs. 49% respectively; p < .001). Adjusted analysis showed reported stimulant use associated with greater odds of physical IPV (adjusted odds ratio [aOR] = 2.0; 95% confidence interval [CI] [1.4, 2.8], p < .001) but not sexual IPV (aOR = 1.3; 95% CI [0.8, 2.0], p = .332). Models stratified by HIV status yielded similar results. Findings showed a high prevalence of past-year IPV experiences among MSM in Los Angeles. Findings highlight links between SU and IPV and underscore a significantly increased likelihood of IPV for MSM in Los Angeles who report current methamphetamine use. This study provides evidence to support universal IPV screening and to make available safety resources at all points where MSM seek healthcare.